The profession of the internal auditor in organizations: what particularities - AZEGAGH, JALAL; KERFALI, Souhaila (Revue du contrôle, de la comptabilité et de l’audit, 2021)
The world of public organizations is constantly changing with, from time to time, outbreaks of fever that accelerate change. And that’s what we experienced with the Enron affair, which forced organizations to be more transparent and more independent in controls. Internal audit cannot remain indifferent to these developments and for more than sixty years, it has strived to be in tune with the concerns of its time and thus contribute to greater security for public organizations, while helping them to improve their performance. As such, the main job of the internal auditor is revealing and contributes perfectly to the good management of organizations. Indeed, the core of the business remains the insurance activity implemented thanks to a prior risk assessment, the added value of which is measured by the objectivity of the findings and the relevance of the recommendations issued. In our article, we present, through a theoretical reflection, the functions of the profession of the internal auditor within public organizations.